The effect of mycorrhizal biofertilizer with the addition of rice washing water and eggshells on the growth of cayenne pepper plant (Capsicum frutescens L.) - Sari, Novita Mulya; Rokhim, Saiku; Faizah, Hanik (Agrovigor, 2024)
Cayenne pepper is a leading horticultural commodity in Indonesia. The need for cayenne pepper is constantly increasing, but it is not balanced with its production because there are obstacles, especially in areas that are less fertile or have low nutrients. This study aims to find out the effect of applying mycorrhizal biological fertilizer by adding rice washing water and eggshells on the growth of cayenne pepper plants. This study used the Complete Randomized Design method. The data were analyzed using One Way Anova (significant level of 5%) and an alternative test Kruskal-Wallis H. The results showed mycorrhizal biological fertilizer 5 gr + rice washing water 200 ml and eggshells 20 gr optimally affecting the number of leaves, branches, and roots, dry weight of the crown. Mycorrhizal biofertilizer 10 gr + rice washing water 150 ml and eggshell 15 gr have an optimal effect on wet weight of the crown and the roots. Mycorrhizal biofertilizer 15 gr + rice washing water 200 ml and eggshell 20 gr have an optimal effect on root length. Mycorrhizal biofertilizer 2 gr + rice washing water 150 ml and eggshell 15 gr have an optimal effect on dry weight of roots.